Intervention programme to improve emotional regulation among adolescent with mental disorders: a systematic review - Kholifah, Siti; Khuzaimah Ahmad Sharoni, Siti; Yusuf, Ah (Intelektual Pustaka Media Utama, 2024)
Adolescence is an important period for developing social and emotional habits that are important for mental well-being. This research aimed to know the effectiveness of intervention programs to improve emotional regulation in adolescents with mental disorders. Preparation using the PICO approach, determination of inclusion and exclusion criteria, and a literature review of scientific English articles published between 2016 and 2023 were conducted. Data were obtained from the SCOPUS, Science Direct, SpringerLink, ProQuest, and SAGE databases. Assessment of the title, abstract, and full text of the article with the keywords